Biological systems for treatment and valorization of wastewater generated from hydrothermal liquefaction of biomass and systems thinking: A review. (April 2019) - Gu, Yexuan; Zhang, Xuesong; Deal, Brian; Han, Lujia
Graphical abstract: Biological systems for treatment and valorization of wastewater from hydrothermal liquefaction of biomass: a perspective and review of recent progress. Highlights: Characterization of wastewater from HTL of biomass was summarized. HTL wastewater valorization by various biological systems is demonstrated. Systems-thinking concept is first proposed to evaluate the valorized systems. Integrated biological-physicochemical systems are significantly illustrated. Perspectives and milestones for HTL wastewater valorization are discussed. Abstract: Hydrothermal liquefaction (HTL) is one of the most promising platforms to valorize diverse biomass. Yet, a large amount of wastewater is produced containing a large amount of recalcitrant substances. Valorization of the refractory wastewater by biological systems to recapture organic matter and nutrients is not only clearly beneficial for the environment but also good for energy recovery. To this end, this study reviews the valorization of HTL wastewater via biological systems from many points of view, starting with the brief characterization of wastewater derived from HTL of diverse biomass. The fundamentals, pros and cons, and the most recent outcomes of numerous biological systems are comprehensively demonstrated with emphasis on their combinations. We then use a systems-thinking concept to shed light on a procedural model exhibiting a new perspective to consolidate the utilization of these systems. Finally, this review elucidates the future perspectives of HTL wastewater valorization.